PENGARUH SUPERVISI KEPALA SEKOLAH DAN KOMPETENSI PEDAGOGIK GURU TERHADAP KINERJA GURU SD SE-KECAMATAN PANGKALAN KERINCI KABUPATEN PELALAWAN - Tri Romawi; Isjoni Isjoni; Afrianto Daud (Tunjuk Ajar: Jurnal Penelitian Ilmu Pendidikan, 2022)
This study aims to determine the effect of principal supervision and pedagogical competence of teachers on the performance of elementary school teachers in Pangkalan kerinci sub-district of pelalawan district.  The population in this study was all teachers of SD Se, Pangkalan Kerinci District, Pelalawan Regency, totaling 180 respondents, and the research sample was 30 respondents. The data analysis used is correlation analysis, correlation coefficient, and coefficient of determination. The results of this study show that there is a positive influence between the principal's supervision (X1) on Teacher Performance (Y) and the Determinant Coefficient = (0.774)2 x100 = 60%. There is also a positive influence between Paedagogic Competence (X2) and Teacher Performance (Y) with Determinant Coefficient = (0.742 )2 x100 = 5.50%. While the Influence of Principal Supervision (X1) and Paedagogic Competence (X2) on Teacher Performance (Y) has a determination coefficient of r2y1.2 = (0.839)2 x100 = 70.4 %. Conclusions from the variables of Principal Supervision and Paedagogic Competence with variables of elementary teacher performance in Pangkalan Kerinci District, Pelalawan Regency has a positive direction.